The effectiveness of the use of innovative methods in teaching Russian language and literature. - Mirzaliev T.G, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Society at the present stage of its development imposes new, higher requirements for the quality of education, which implies a rethinking of the educational process. One of the essential aspects of this problem is the intensive assimilation of artistic, literary and journalistic phraseological units that have arisen in the popular environment and have become, thanks to the exceptional richness of content and perfection of form, a traditional means of expression.